2004
DOI: 10.1128/iai.72.7.3724-3732.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium aviumsubsp.paratuberculosisFibronectin Attachment Protein Facilitates M-Cell Targeting and Invasion through a Fibronectin Bridge with Host Integrins

Abstract: Paratuberculosis is a chronic granulomatous enteritis of domestic and wild ruminants that is caused by Mycobacterium avium subsp. paratuberculosis, a slow-growing intracellular acid-fast bacillus. Animals are usually infected within the first few months of life; however, the chronic wasting and profuse diarrhea that characterize clinical paratuberculosis are usually not observed until 3 or more years after infection (4, 7).M. avium subsp. paratuberculosis enters intestinal tissue through M cells present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
75
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 38 publications
4
75
0
4
Order By: Relevance
“…Whether the mechanisms of interaction are the same is currently unknown. Bacterial genes required for the invasion of bovine epithelial cells have been identified (1), but all the evidence so far supports the hypothesis that uptake by M cells follows binding to the ␤ 1 integrin receptor (15,23,24). Our study confirmed that in vitro, invasion of MDBK cells by M. avium subsp.…”
Section: Discussionsupporting
confidence: 78%
“…Whether the mechanisms of interaction are the same is currently unknown. Bacterial genes required for the invasion of bovine epithelial cells have been identified (1), but all the evidence so far supports the hypothesis that uptake by M cells follows binding to the ␤ 1 integrin receptor (15,23,24). Our study confirmed that in vitro, invasion of MDBK cells by M. avium subsp.…”
Section: Discussionsupporting
confidence: 78%
“…In this study we report M. hyopneumoniae as a bacterial pathogen capable of binding fibronectin. The ability of bacteria to bind fibronectin can provide a mechanism for host cell adhesion or cytoskeletal rearrangements, which may facilitate bacterial internalization (41)(42)(43)(44)(45). SPR analysis demonstrated that F4 P116 -bound fibronectin in a dose-dependent manner with a physiologically relevant K D value.…”
Section: Discussionmentioning
confidence: 99%
“…Like other intracellular pathogens, such as Yersinia spp., Salmonella enterica serovar Typhimurium, and Shigella spp., M. avium subsp. paratuberculosis infects M cells due to their lack of hydrolytic enzymes and inability to form mature phagosomes (6,27,28,41,42,44). However, further investigations have revealed that M. avium subsp.…”
mentioning
confidence: 99%